1977
DOI: 10.3189/s0022143000215736
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the structure and strength of ice on solid surfaces

Abstract: Experimental and theoretical investigations have made it possible to define more exactly some features of ice formation on solid surfaces

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Solute concentrations tend to be uniform within the brine pocket and, thus, with a uniform freezing point, results in supercooling and freezing at the cooler end of the pocket, and superwarming and ice melting at the warmer extreme. More explicitly, some researchers [e.g., Penner , ; Voytkovskiy and Golubev , ] determined that freezing rates of pure water and solutions are minimal when temperature is held close to the freezing point, at which the ice‐water interface is close to equilibrium, but the rates will increase, many fold, at higher extents of supercooling. Voytkovskiy and Golubev [] even suggest that the freezing rate of water is proportional to the cubic root of the extent of supercooling, which means that the freezing rate is technically zero when the ice‐water interface reaches equilibrium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solute concentrations tend to be uniform within the brine pocket and, thus, with a uniform freezing point, results in supercooling and freezing at the cooler end of the pocket, and superwarming and ice melting at the warmer extreme. More explicitly, some researchers [e.g., Penner , ; Voytkovskiy and Golubev , ] determined that freezing rates of pure water and solutions are minimal when temperature is held close to the freezing point, at which the ice‐water interface is close to equilibrium, but the rates will increase, many fold, at higher extents of supercooling. Voytkovskiy and Golubev [] even suggest that the freezing rate of water is proportional to the cubic root of the extent of supercooling, which means that the freezing rate is technically zero when the ice‐water interface reaches equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…More explicitly, some researchers [e.g., Penner , ; Voytkovskiy and Golubev , ] determined that freezing rates of pure water and solutions are minimal when temperature is held close to the freezing point, at which the ice‐water interface is close to equilibrium, but the rates will increase, many fold, at higher extents of supercooling. Voytkovskiy and Golubev [] even suggest that the freezing rate of water is proportional to the cubic root of the extent of supercooling, which means that the freezing rate is technically zero when the ice‐water interface reaches equilibrium. Therefore, Spaans and Baker [] suggested that the thermodynamic equilibrium assumption of the Clapeyron equation may never be reached, or may take a very long time to establish.…”
Section: Introductionmentioning
confidence: 99%